Symptoms and their Relationship to Disability Following Treatment for Lower Extremity Tumours. (1999) - Davis, Aileen M.; Punniyamoorthy, Sajeevan; Griffin, Anthony M.; Wunder, Jay S.; Bell, Robert S.
Abstract : Purpose. The aims of this study were to describe the symptoms experienced by patients in the first year following treatment for lower extremity sarcoma by limb conservation and to describe the relationship between symptoms and physical disability. Subjects. Eighty consecutive patients treated for primary bone or soft tissue sarcoma (STS) of the lower limb who were treated with limb preservation surgery. Methods. Subjects were evaluated by questionnaire at 6 weeks, and 3, 6, and 12 months post surgery. They identified whether they experienced any of the following symptoms: pain, stiffness, fatigue, weakness, limited range of motion, or swelling.The Toronto Extremity Salvage Score (TESS), a measure of physical disability, was also completed. Frequency of symptoms over time was calculated and change was evaluated using the Cochrane test. The relationship of symptoms to disability was analyzed with regression methods. Results. The mean age was 43.0, SD=20.4 with a gender ratio of 1:1. There were 38 bone tumours and 42 STS.The most frequently reported symptoms were: stiffness 48 (60%), weakness 41 (51%), fatigue 26 (33%), and pain 25 (31%) at 6 weeks. Stiffness and fatigue decreased and plateaued by 3 months. Complaints of weakness and pain continued to decrease over time. At 6 weeks, pain, stiffness, weakness and limited motion predicted disability in both univariate and multivariate analyses. At 12 months, pain, stiffness, fatigue, weakness and limited motion were significant predictors of the TESS in univariate analysis with only pain, stiffness and limited motion significant predictors in the multivariate model. Discussion. Pain, stiffness, fatigue, weakness and limited motion are common symptoms with stiffness and weakness decreasing significantly over time. The symptoms predictive of disability differ between the acute and late phases of recovery.